PROSPEK PENGEMBANGAN RUMPUT LAUT DI KABUPATEN MOROWALI - Zakirah Raihani Ya'la (Universitas Tadulako, 2008)
The research aim was to obtain a broader general feature on fishery and oceanic potency especially seaweeds. The method used in this research was primary and secondary data collection. The primary data were collected through field observation targeted all stakeholders covering elite figures, governmental functionary, international corporate groups and industry, district KADIN, observer, and society members such as preserver of fish/ preserver of seaweed go out to sea and fisherman. The secondary data were collected from various institutions such as Bappeda of Central Sulawesi Province and its districts, and other related institutions. Results of the research showed that in Morowali district, there are economically valuable diverse sea weeds. Such seaweeds include Eucheuma cottonii, Eucheuma spinosum, and Gracillaria. The seaweeds are potential to be developed in such regions as South Bungku sub-district, Menui Islands sub-district, and Witaponda sub-district.